Not so standard anymore? Employment duality in Germany - Eichhorst, Werner; Tobsch, Verena (Bonn, 2014)
"This paper gives an overview of the transformation of the German labour market since the mid-1990s with a special focus on the changing patterns of labour market segmentation or 'dualization' of employment in Germany. While labour market duality in Germany can partially be attributed to labour market reforms promoting, in particular, non-standard forms of employment and allowing for an expansion of low pay, structural changes in the economy as well as strategic choices by employers and social partners also play a prominent role. Our main argument is that the liberalization of non-standard contracts has contributed to the expansion of overall labour market inclusion and job growth in Germany and that at least some forms of non-standard work provide stepping stones into permanent regular jobs. Atypical contracts do not necessarily undermine the dominance of standard employment relationships and job quality in this primary segment but rather form a supplementary part of employment in sectors that depend on more flexible and maybe cheaper forms of labour."